Ultra-lightweight space arm DELIAN: mechatronic analysis and joint control design. Issue 1 (July 2017) - Cavenago, Francesco; Bascetta, Luca; Magnani, Gianantonio; Rusconi, Andrea
Abstract: This paper deals with the design of the control system for a joint prototype of ESA space manipulator DELIAN. A joint model is developed, focusing on assessment of joint structural parameters and most important torque disturbances, mainly related to dependence of friction on velocity, position and temperature. Then, analysis and design of the P/PI controller are carried out, giving stability conditions, and proposing an optimal tuning for velocity and position loops, with respect to setpoint tracking and disturbance rejection requirements.